GRCBox: Extending Smartphone Connectivity in Vehicular Networks - Sergio M. Tornell; Subhadeep Patra; Carlos T. Calafate; Juan-Carlos Cano; Pietro Manzoni (International Journal of Distributed Sensor Networks)
The low penetration of connectivity-enabled OBUs is delaying the deployment of vehicular networks (VNs) and therefore the development of vehicular delay tolerant network (VDTN) applications, among others. In this paper we present GRCBox, an architecture based on RaspberryPi that allows integrating smartphones in VNs. GRCBox is based on a low-cost device that combines several pieces of software to provide ad hoc and multi-interface connectivity to smartphones. Using GRCBox each application can choose the interface for its data flows, which increases flexibility and will allow developers to easily implement applications based on ad hoc connectivity, such as VDTN applications.